Development and validation of a questionnaire in Hindi language to assess Parental Knowledge, Attitude and Practices regarding Calcium and Vitamin D deficiency in children - Chand, Suresh; Singh, Shivendra Kumar; Tripathi, Shalini; Afaque, Syed Faisal; Pandit, Pratyaksha; Singh, Ajai (Indian Journal of Community Health, 2024)
Background: Despite being in temperate zone, India is endemic to nutritional rickets. However, very little has been studied on knowledge, perception and cultural practices of Indian communities, towards calcium and vitamin-D deficiency in children. Aim & Objective: The study aimed to develop and validate a questionnaire in Hindi language for the assessment of knowledge, attitude, and practices of parents towards calcium and vitamin D deficiency among children. Methodology: We searched electronic databases for item generation. The questionnaire was developed in Hindi language by five experts in the field of pediatrics, pediatric orthopaedics and community medicine using Delphi method. After language correction from Hindi language experts, a convenient sample of 30 participants filled the questionnaire and tested for internal consistency and test-retest reliability. Results: The overall Cronbach’s alpha value for the finalized 46-item scale indicated an acceptable reliability (alpha = 0.91). The internal consistency reliability for six domains created was acceptable. The results revealed ‘high’ test-retest reliability, and there was no statistically significant difference noted between any of the first test and re-test corresponding values (p>0.05). Conclusion: The present questionnaire developed in Hindi Language to assess knowledge, attitude and practices (KAP) of parents towards Calcium & Vitamin-D deficiency in children, has a good validity and reliability. This newly developed instrument could prove its use to highlight the gaps that may exist among parents. The use of this tool may help clinicians, health educators and policy makers to identify key areas of intervention with regards to Calcium & Vitamin-D deficiency in children.